Cell surface GRP78 signaling: An emerging role as a transcriptional modulator in cancer. Issue 4 (31st August 2020) - Gopal, Udhayakumar; Pizzo, Salvatore V.
Abstract: Cancer cells acquire dysregulated gene expression to establish specific transcriptional dependencies and their underlying mechanisms that are ultimately responsible for this addictions have not been fully elucidated. Glucose‐regulated protein 78 (GRP78) is a stress‐inducible, multifunctional, prosurvival, endoplasmic reticulum chaperone in the heat shock protein 70 family. Expression of cell surface GRP78 (CS‐GRP78) is associated with increased malignant behavior and resistance to chemotherapy and radiotherapy by endowing various cancer cells with increased proliferative ability, altered metabolism, improved survival, and augmented invasive and metastatic potential. Emerging evidence has highlighted an unusual role of CS‐GRP78 in regulating transcription factors (TFs) by mediating various signaling pathways involved in malignant transformation, metabolic reprogramming, and tumor progression. During the last decade, we targeted CS‐GRP78 with C38 monoclonal antibody (C38 Mab) in numerous studies, which have highlighted the epigenetic interplay between CS‐GRP78 and various TFs including c‐MYC, Yes‐associated protein/transcriptional coactivator with PDZ‐binding motif, c‐Fos, and histone acetylation to potentiate subsequent modulation of tumorigenesis, invasion, and metastasis. Here, we summarize the current state of knowledge about the role of CS‐GRP78 in cancer development and progression, including epigenetic regulation and sheds light on CS‐GRP78 as vulnerable target for cancer therapy. Overall, this review focuses on the mechanisms of TFs that are behind the transcriptional dysregulation in cancer and lays the groundwork for rational therapeutic use of C38 Mab based on CS‐GRP78 biology. Abstract : This study is the first review to describe mechanisms of transcriptional regulation triggered by ligation of cell surface glucose‐regulated protein (GRP78). While this protein was originally characterized as an endoplasmic reticulum chaperone, a significant body of work now demonstrates that GRP78 reaches the cell surface of injured or malignant cells where it functions as a typical signaling receptor linked to proproliferative, antiapoptotic, and promigratory signaling cascades.